KONTRIBUSI PENGARUH JOB INSECURITY, KOMITMEN ORGANISASI, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION DI HOTEL YELLOW STAR YOGYAKARTA - An Arya Putra, Rendy; Nuvriasari, Audita (MANAJEMEN DEWANTARA, 2024)
This study analyzes the influence of Job Insecurity, organizational commitment, and job satisfaction on Turnover Intention at Yellow Star Hotel Yogyakarta. The following research uses a quantitative approach. The sample of this study was all 83 employees of Yellow Star Hotel Yogyakarta. The results of this study indicate that job insecurity has a positive and significant effect on turnover intention. It also shows that the higher the job insecurity, the higher the turnover intention. Furthermore, organizational commitment has a negative and significant effect on turnover intention. The results of this study indicate that the higher the organizational commitment of employees will reduce the level of turnover intention. In addition, job satisfaction has a negative and significant effect on turnover intention. The results of this study indicate that the higher the employee's job satisfaction, the lower the level of turnover intention. The result of this study are expected to be one of the bases for evaluation in human resources management.